Efeito do treinamento auditivo em habilidades fonológicas de crianças com transtorno do desenvolvimento da fala e da linguagem - Teixeira, Bruna Sana [UNIFESP] (2018)
Aim: To verify the effect of auditory training on phonological and metaphonological skills of children with Speech Sound Disorder (SSD) and Developmental Language Disorder (DLD). Methods: This was a longitudinal and prospective intervention study. Six children participated in the study, three with SSD and three with DLD, aged from 5:9 to 7:9 years. Each child participated in two intervention moments, with 10 sessions of 45 minutes each: one, control, in which the child received Language Therapy only (L Therapy); and another, experimental, in which language therapy was associated with auditory training (AL Therapy). Before and after each intervention moment (L Therapy and AL Therapy), auditory skills, Percentage of Correct Consonants (PCC) and Phonological Awareness (PA) were evaluated (EV). The sequence of procedures adopted for all children was: EV1, L Therapy, EV2, AL Therapy, and EV3. The calculation used to measure if the improvement with AL Therapy was higher than with L Therapy was: Effect = (EV3 – EV2) ( EV2 EV1). Results: Half of the sample (two with SSD and one with DLD) had a real positive Effect in the PCC, that is, they improved more with AL Therapy compared to L Therapy. Also half of the subjects (two with SSD and one with DLD) had a real positive Effect in PA. Although there was a huge variability, the Effect mean showed bigger improvements with AL Therapy compared to L Therapy, both for PCC and PA. Conclusion: Despite the short length of the program and variability of response, half of the children improved more in phonological and metaphonological skills when the language therapy was combined with the auditory training. Furthermore, selective attention seems to have been more related to PCC, while temporal processing seems to have been more related to PA. In fact, for some children, there seems to be a more pronounced improvement in phonology and phonological awareness when auditory processing training is included in language therapy, even for a short period of training. Children with speech and language disorders are heterogeneous and each case should be analyzed individually.